ANALISIS PERBANDINGAN RISIKO KERUSAKAN DAN KERUGIAN EKONOMI BANGUNAN RUMAH TINGGAL DAN SEKOLAH AKIBAT GEMPA BUMI DI JAWA TIMUR - Reza Zulkarnain, Muhammad
Indonesia is in an active ring of fire due to the movement of tectonic plates. This condition makes Indonesia vulnerable to earthquakes. One of the areas in Indonesia that is prone to earthquakes is East Java. Even the large Mw 7.8 earthquake that caused a tsunami had occurred in East Java in 1994. The Kendeng Fault is an active fault that extends from the middle of East Java to the eastern part of Central Java. Medium-sized shallow earthquakes (M4-5) have occurred along this fault zone in recent years. This earthquake will certainly cause casualties, losses, and damage to buildings, especially residential buildings and schools. This makes earthquakes a disaster to watch out for. This condition causes risk management to be applied to reduce impacts such as estimating damage and economic losses caused by earthquake disasters, especially in earthquake-prone areas such as East Java. This study aims to calculate the risk of damage and economic loss to residential and school buildings due to the earthquake in East Java. This research is expected to help the government in disaster mitigation efforts. The calculation of the risk of damage and economic loss is carried out using OpenQuake software with the event-based probabilistic damage method and risk analysis using several data, namely exposure models of residential and school buildings, vulnerability models, fragility models and earthquake hazard data. School buildings have a smaller risk of damage than residential buildings with the risk of loss of residential buildings annually amounting to 1.7 trillion while the loss of school buildings is 17.5 billion.